Dual response foam stabilizer and method of making same

By growing silica in situ on the core layer of porous cellulose microspheres and grafting amphoteric surfactants, an outer copolymerization is formed to form a responsive shell, which solves the stability problem of foam fluid under complex reservoir conditions, realizes dual response to temperature and pH and synergistic slow-release function, and improves the stability and shear resistance of foam.

CN123026751APending Publication Date: 2026-11-03东营市工业产品检验与计量检定中心 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611517406.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing foam fluids have poor stability under complex reservoir conditions such as high temperature and high salinity, cannot adapt to pH changes, and lack the synergistic effect of sustained release of functional components.

Method used

Porous cellulose microspheres are used as the core layer, and silica is grown in situ in the pores and on the surface. Amphoteric surfactants are grafted onto the core layer. The outer layer is coated with a responsive shell formed by copolymerization of N-isopropylacrylamide, dimethylaminoethyl methacrylate and a silane coupling agent containing double bonds, so as to achieve dual response to temperature and pH.

Benefits of technology

In complex reservoir environments, foam stabilizers have dual functions of temperature and pH response. The amphoteric surfactants in the core layer are released slowly, and the shell layer responds and is driven to migrate by hydrophobicity, forming a Si-O-Si cross-linked network, which significantly improves the shear resistance and stability of the foam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123026751A_ABST
    Figure CN123026751A_ABST
Patent Text Reader

Abstract

The application discloses a dual-response foam stabilizer and a preparation method thereof, and belongs to the technical field of oil field chemicals. The foam stabilizer comprises a core layer and a responsive copolymer shell layer coated on the outer surface of the core layer; the core layer is composed of porous cellulose microspheres, silica grown in the channels of the porous cellulose microspheres and on the surface of the microspheres, and amphoteric surfactant grafted on the surface of the silica; and the responsive copolymer shell layer is obtained by copolymerization of N-isopropyl acrylamide, dimethylaminoethyl methacrylate and a silane coupling agent containing a double bond. After the porous cellulose microspheres are modified by epoxidation and carboxymethylation, the silica is grown in the channels and on the surface of the microspheres in situ, efficient grafting of the amphoteric surfactant is realized through amination modification, and finally, the copolymer shell layer with temperature / pH dual response is coated on the surface of the core layer, so that the foam stabilizer has the dual response capability of temperature response and pH response, and has excellent foam stabilizing performance in a complex oil reservoir environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a dual-response foam stabilizer and its preparation method, belonging to the field of oilfield chemical technology. Background Technology

[0002] Foam fluids possess advantages such as good compressibility, low frictional resistance, small liquid volume, minimal reservoir damage, and strong solid particle carrying capacity, making them widely used in various processes within the petroleum industry. However, foam stability is a crucial factor in practical applications. Traditional foam systems exhibit poor stability under complex reservoir conditions such as high temperature and high salinity, with foam prone to aggregation and coarsening, leading to decreased oil displacement efficiency.

[0003] Patent CN113912780B discloses a temperature-responsive nano-foam stabilizer and its preparation method. This nano-foam stabilizer consists of PDEA-PS latex particles. The PDEA segments transition from a highly hydrated state to a dehydrated state upon heating, causing the particles to flocculate and adsorb at the gas / liquid interface to form a solidified film, thereby enhancing foam stability. However, this technical solution has the following shortcomings: First, the response mechanism is singular: it relies solely on temperature triggering and cannot adapt to conditions such as pH changes in complex oil reservoir environments; second, the core layer is composed of solid latex particles, lacking functional loading capacity and failing to achieve sustained-release synergy of functional components.

[0004] In addition, although there are reports of cellulose nanocrystal grafted poly(2-dimethylaminomethyl methacrylate) copolymers achieving dual temperature and pH responses in the existing technology, these copolymers only achieve responses through changes in molecular chain conformation and lack the strengthening mechanism of interfacial chemical cross-linking, resulting in poor stability.

[0005] Therefore, developing a novel foam stabilizer with dual response and sustained-release synergistic function is of great significance for the application of foam fluids in complex reservoir environments. Summary of the Invention

[0006] To address the aforementioned issues, a dual-responsive foam stabilizer is provided. This stabilizer is achieved by in-situ growth of silica within and on the surface of porous cellulose microspheres, followed by grafting of an amphoteric surfactant to obtain a core layer. Finally, a copolymer shell layer with dual temperature / pH responsiveness is coated onto the surface of the core layer, giving the foam stabilizer both temperature and pH responsiveness.

[0007] According to a first aspect of this application, this application provides a dual-responsive foam stabilizer, comprising a core layer and a responsive copolymer shell layer covering the outer surface of the core layer; The core layer consists of porous cellulose microspheres, silica grown in the channels of the porous cellulose microspheres and on the surface of the microspheres, and amphoteric surfactants grafted onto the surface of the silica. The responsive copolymer shell is obtained by copolymerizing N-isopropylacrylamide, dimethylaminoethyl methacrylate, and a silane coupling agent containing double bonds.

[0008] The foam stabilizer of this application comprises a core layer and a responsive copolymer shell layer coating the outer surface of the core layer. The porous cellulose microspheres in the core layer provide a flexible framework with a high specific surface area. In-situ growth of silica within the pores and on the surface endows the core layer with Pickering foam stabilizing ability and mechanical reinforcement. Furthermore, grafting an amphoteric surfactant onto the silica surface enables the core layer itself to possess interfacial activity. Upon temperature or pH response of the foam stabilizer, the shell layer becomes hydrophobic. The hydrophobic segments of the surfactant facilitate migration and accumulation at the gas / liquid interface, thereby continuously exerting a foam-stabilizing effect during foam drainage.

[0009] The amphoteric surfactant grafted in the core layer is continuously and slowly released during foam drainage, replenishing the interfacial active molecules. The responsive function of the shell layer drives the entire core-shell structure to migrate to the gas / liquid interface, allowing the slow-release function of the core layer to be concentrated at the interface. The two layers form a clear complementary division of labor. Without either the core or shell layer, it is difficult to achieve a complete response-migration-anchoring-slow-release foam stabilization mechanism.

[0010] The LCST of N-isopropylacrylamide (NIPAM) in the responsive shell is 32-40℃, which can provide temperature response capability: when the system temperature rises above the LCST, the PNIPAM chain segments in the shell undergo dehydration and collapse, the surface of the foam stabilizer changes from hydrophilic to hydrophobic, forming a hydrophobic barrier on the bubble surface, reducing the liquid film drainage rate, and delaying foam coarsening and aggregation.

[0011] Dimethylaminoethyl methacrylate (DMAEMA) has a tertiary amine group with a pKa of approximately 7.0, enabling it to provide a pH response: under neutral to alkaline conditions, the tertiary amine group undergoes deprotonation, restoring to a neutral tertiary amine, making the shell uncharged. The chain segments collapse due to hydrophobic interactions, and the surface of the foam stabilizer changes from hydrophilic to hydrophobic, promoting the migration of the foam stabilizer to the gas / liquid interface to form a hydrophobic barrier. When the pH decreases, DMAEMA is reprotonated, the shell regains its hydrophilicity, and the foam stabilizer partially desorbs from the interface, thereby achieving reversible control of foam stability.

[0012] After the shell responds to hydrophobicity, the foam stabilizer migrates from the aqueous phase to the gas / liquid interface, and the amphoteric surfactant grafted in the core layer is enriched at the interface along with the core-shell structure, and its concentration is significantly increased at the interface, thereby achieving concentrated release.

[0013] The silane groups in silane coupling agents containing double bonds do not participate in the polymerization stage of the shell copolymer. During the foaming stage, after the foam stabilizer migrates to the gas / liquid interface, it can form a three-dimensional Si-O-Si cross-linked network through hydrolysis and condensation, firmly anchoring the foam stabilizer to the gas / liquid interface. Simultaneously, the Pickering effect of silica in the core layer and the synergistic effect of the interfacial activity of the amphoteric surfactant, together with the silane coupling agent, form a composite interfacial barrier at the bubble interface consisting of a solid particle adsorption layer, a surfactant molecular layer, and a chemical cross-linked network, thereby significantly improving the shear resistance of the foam.

[0014] Optionally, the porous cellulose microspheres are obtained by epoxidation modification and carboxymethylation modification.

[0015] Epoxidation and carboxymethylation modifications of porous cellulose microspheres facilitate subsequent amination and electrostatic adsorption grafting of amphoteric surfactants. The synergistic effect of these two modifications significantly improves the functionalization efficiency and grafting uniformity of the core layer.

[0016] Optionally, the amphoteric surfactant is cocamidopropyl hydroxysulfonate or dodecyl dimethyl sulfonate.

[0017] Both of these amphoteric surfactants belong to the sulfobetaine class. Sulfobetaine amphoteric surfactants have excellent temperature and salt resistance. Their sulfonic acid groups are not affected by pH and can maintain interfacial activity over a wide pH range. This complements the pH response mechanism of DMAEMA, ensuring that the foam stabilizer can continuously play a foam-stabilizing role in complex reservoir environments.

[0018] Optionally, the silane coupling agent containing double bonds is at least one of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, 3-(acryloxy)propyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.

[0019] According to a second aspect of this application, this application provides a method for preparing the dual-responsive foam stabilizer described in any of the above claims, comprising the following steps: (1) Preparation of porous cellulose microspheres S1 dissolves cellulose in water to obtain a cellulose aqueous solution with a cellulose mass fraction of 10-20%, adds a physical porogen with a cellulose mass fraction of 30-50%, adjusts the pH to 10-12, and obtains the aqueous phase; S2. After adding a dispersant to the oil phase solvent and dispersing it evenly, an oil phase is obtained. A water phase is then added dropwise to it under stirring. The volume ratio of the oil phase to the water phase is (5-10):1. After the dropwise addition is completed, a crosslinking agent is added. The temperature is raised to 50-60℃, and the reaction is carried out for 3-6 hours under stirring at a stirring rate of 300-500 rpm. After the S3 reaction is completed, the microspheres are obtained by filtration and separation. Then, the microspheres are immersed in HCl solution and stirred until no more bubbles are generated. Finally, they are washed and dried to obtain porous cellulose microspheres. (2) Modification of porous cellulose microspheres S4. Porous cellulose microspheres were dispersed in NaOH solution, and epichlorohydrin was added. The volume ratio of epichlorohydrin to the mass ratio of porous cellulose microspheres was 0.5-2 ml / g. The reaction was carried out at 30-40℃ for 4-6 h. After the reaction was completed, the microspheres were filtered, washed, and dried to obtain epoxidized cellulose microspheres. S5. Epoxidized cellulose microspheres were dispersed in a mixed solvent of isopropanol and water, and equimolar amounts of sodium chloroacetate and NaOH were added. The mass of sodium chloroacetate was (1.5-2.5):1 of the mass of the epoxidized cellulose microspheres. The mixture was stirred at 55-60℃ for 3-4 hours, filtered, washed, and dried to obtain modified porous cellulose microspheres. (3) The modified porous cellulose microspheres were dispersed in anhydrous ethanol and ultrasonically dispersed to obtain a dispersion. Ammonia water was added, and the volume ratio of ammonia water to the mass ratio of modified porous cellulose microspheres was 0.5-1 ml / g. An ethanol solution containing tetraethyl orthosilicate was added dropwise to the dispersion under stirring, and the volume ratio of tetraethyl orthosilicate to the mass ratio of modified porous cellulose microspheres was 1.5-2.5 ml / g. After the dropwise addition was completed, the mixture was reacted under stirring for 4-6 hours. After the reaction was completed, the mixture was separated, washed, and dried to obtain cellulose-silica composite microspheres. (4) Disperse cellulose-silica composite microspheres in anhydrous toluene, and after ultrasonic dispersion, add 3-5% of 3-aminopropyltriethoxysilane by mass of cellulose-silica composite microspheres. Heat to 80-110℃ and reflux for 12-24 h under inert gas protection. After the reaction, filter, wash and dry to obtain aminated composite microspheres. (5) Disperse the aminated composite microspheres in water, adjust the pH to 3.5-4.5, add an aqueous solution containing an amphoteric surfactant, the mass of which is 5-15% of the mass of the aminated composite microspheres, stir for 2-4 hours, adjust the pH to 7-8, filter, wash, and dry to obtain the core layer; (6) Disperse the core layer in a mixed solvent of ethanol and water, add a silane coupling agent containing double bonds, adjust the pH to 4-5, stir at room temperature for 2-4 h, and then add N-isopropylacrylamide, dimethylaminoethyl methacrylate, and initiator. The ratio of the total mass of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and silane coupling agent containing double bonds to the mass of the core layer is (0.3-0.8):1, and the molar ratio of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and silane coupling agent containing double bonds is (14-16):(3-5):1. React at 60-70℃ under a protective gas atmosphere for 4-6 h. After the reaction is completed, separate, wash, and dry to obtain the final product.

[0020] Step (1) Porous cellulose microspheres are prepared by reverse suspension crosslinking method. After adding physical pore-forming agent and removing it by HCl, a porous structure is formed, which provides sufficient space for in-situ growth of silica and grafting of surfactant.

[0021] Step (2) involves surface functionalization of porous cellulose microspheres through epoxidation and carboxymethylation. Epichlorohydrin undergoes a ring-opening reaction with the hydroxyl groups of cellulose under alkaline conditions, introducing chlorohydroxypropyl active sites on the surface and inner walls of the microspheres, providing reaction anchors for subsequent amination modification. Sodium chloroacetate reacts with the epoxidation sites to introduce carboxymethyl groups, increasing the surface negative charge density, which is beneficial for subsequent amination modification and electrostatic adsorption grafting of amphoteric surfactants. In addition, the improved surface roughness and chemical activity of the modified microspheres are conducive to the uniform nucleation of tetraethyl orthosilicate and the permeation polymerization of shell monomers.

[0022] In step (3), the ammonia provides an alkaline catalytic environment, allowing tetraethyl orthosilicate to hydrolyze and condense within the microsphere channels. Silica preferentially nucleates and grows on the inner walls of the channels, bonding firmly with cellulose via Si-OC bonds. The in-situ grown silica imparts Pickering foam-stabilizing ability to the core layer, while significantly improving its thermal stability and mechanical strength, thus ensuring the structural stability of the nano-foam stabilizer in high-temperature oil reservoir environments.

[0023] Step (4) involves amination modification of the cellulose-silica composite microspheres using 3-aminopropyltriethoxysilane (APTES). The ethoxy groups of APTES can condense with the silanol groups on the silica surface, introducing aminopropyl groups into the surface and pores of the microspheres, providing anchoring sites for the grafting of amphoteric surfactants. Furthermore, the amination modification results in a positively charged microsphere surface, which is beneficial for the subsequent electrostatic adsorption grafting of sulfobetaine under acidic conditions.

[0024] Step (5) Under acidic conditions, the ammonium ions on the surface of the aminated microspheres are electrostatically attracted to the sulfonate ions of sulfobetaine, thereby achieving electrostatic grafting.

[0025] Step (6) achieves shell coating through a pre-anchoring followed by polymerization: the double-bonded silane coupling agent first condenses with the core surface via silanoxy groups, anchoring the C=C double bonds to the core layer, and then initiates NIPAM and DMAEMA copolymerization. This method can improve the accuracy of the copolymer coating the core surface and ensure that the shell does not desorb under shear conditions. The copolymerization of the three components enables the shell to achieve both temperature and pH responsiveness, and also enhances the mechanical strength of the bubble liquid film, inhibiting bubble rupture. The ratio of the total monomer mass to the core mass is (0.3-0.8):1. At this ratio, the shell thickness will not be too thick or too thin, allowing it to fully exert its responsive function.

[0026] Optionally, the cellulose in step S1 is hydroxypropyl methylcellulose or microcrystalline cellulose.

[0027] Optionally, the physical pore-forming agent is at least one of calcium carbonate, magnesium carbonate, and barium carbonate.

[0028] Calcium carbonate, magnesium carbonate, and barium carbonate are all acid-soluble inorganic salts, which can be removed by treatment with dilute HCl to form a porous structure.

[0029] Optionally, the particle size of the physical porogen is 1-5 μm.

[0030] The particle size of the pore-forming agent determines the size of the resulting pores. Within this particle size range, sufficient space capacity can be provided for subsequent in-situ growth of silica and grafting of amphoteric surfactants.

[0031] Optionally, the oil phase solvent in step S2 is at least one of cyclohexane, n-hexane, n-heptane, and cyclopentane.

[0032] Optionally, the dispersant is polyglycerol monostearate or Span 80, and the amount used is 2-4% of the mass of the oil phase solvent.

[0033] Optionally, the crosslinking agent is divinyl sulfone, and the amount used is 20-50% of the cellulose mass.

[0034] The sulfone group of divinyl sulfone can react with the hydroxyl group of cellulose to form a stable ether crosslinking network.

[0035] Optionally, the concentration of the HCl solution in step S3 is 0.5-1.5 mol / L.

[0036] Optionally, the concentration of the NaOH solution in step S4 is 1.5-2.5 mol / L.

[0037] Optionally, the modified porous cellulose microspheres described in step (3) are dispersed in anhydrous ethanol at a concentration of 0.05-0.08 g / mL.

[0038] This dispersion concentration ensures that the microspheres are fully dispersed in the solvent without agglomeration.

[0039] Optionally, the ammonia solution has a mass fraction of 20-30%.

[0040] Ammonia solution with a mass fraction of 20-30% can provide a suitable alkaline catalytic environment to promote the hydrolysis and condensation of tetraethyl orthosilicate.

[0041] Optionally, the volume fraction of tetraethyl orthosilicate in the ethanol solution containing tetraethyl orthosilicate is 25-30%.

[0042] The above volume fraction allows for control of the addition rate and local concentration of tetraethyl orthosilicate, ensuring that silica preferentially grows in situ within the microsphere channels and on the surface.

[0043] Optionally, the dispersion concentration of the porous cellulose microspheres in the NaOH solution in step S4 is 0.04-0.06 g / mL.

[0044] This dispersion concentration ensures that the microspheres are fully dispersed in the solvent without agglomeration.

[0045] Optionally, the dispersion concentration of the epoxidized cellulose microspheres in the mixed solvent in step S5 is 0.04-0.06 g / mL.

[0046] This dispersion concentration ensures that the microspheres are fully dispersed in the solvent without agglomeration.

[0047] Optionally, the dispersion concentration of the cellulose-silica composite microspheres in anhydrous toluene in step (4) is 0.04-0.06 g / mL.

[0048] This dispersion concentration ensures that the microspheres are fully dispersed in the solvent without agglomeration, avoiding the reduction in functionalization efficiency caused by microsphere agglomeration due to excessively high concentration.

[0049] Optionally, the concentration of the aminated composite microspheres in water in step (5) is 0.03-0.05 g / mL.

[0050] This dispersion concentration ensures that the microspheres are fully dispersed in the solvent without agglomeration.

[0051] Optionally, the mass concentration of the aqueous solution containing the amphoteric surfactant is 0.5-5%.

[0052] Optionally, the dispersion concentration of the core layer microspheres in water in step (6) is 0.04-0.06 g / mL.

[0053] Optionally, the initiator is ammonium persulfate or potassium persulfate, and the amount used is 1-3% of the total molar amount of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and silane coupling agent containing double bonds.

[0054] The beneficial effects of this application include, but are not limited to: 1. According to the dual-responsive foam stabilizer of this application, porous cellulose microspheres are used as the core matrix, and silica is grown in situ in the pores and on the surface, and amphoteric surfactants are grafted on. The outer layer is coated with a responsive shell formed by copolymerization of NIPAM, DMAEMA and silane coupling agent containing double bonds. This structure enables the foam stabilizer to have dual functions of temperature response and pH response.

[0055] 2. According to the dual-response foam stabilizer of this application, the amphoteric surfactant grafted in the core layer can achieve slow release during foam drainage, delaying foam coarsening and aggregation; after the shell layer responds, the hydrophobic energy drives the foam stabilizer to migrate to the gas / liquid interface, and the silane coupling agent hydrolyzes and condenses to form a Si-O-Si crosslinked network, chemically anchoring the foam stabilizer to the interface.

[0056] 3. According to the dual-response foam stabilizer of this application, the sulfobetaine amphoteric surfactant in the core layer has excellent temperature and salt resistance, forms functional complementarity with DMAEMA, and synergistically imparts the core layer Pickering foam stabilizing ability with silica, so that the foam stabilizer can maintain structural stability and foam stabilizing performance in complex reservoir environments with high temperature, high salt and wide pH range.

[0057] 4. According to the preparation method of the dual-response foam stabilizer of this application, the core layer and shell layer are prepared efficiently through stepwise preparation, with mild conditions and good repeatability. Attached Figure Description

[0058] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a graph showing the trend of half-life variation of the dual-response foam stabilizer prepared in Example 3 of this application at different temperatures; Figure 2 The graph shows the trend of half-life of the dual-response foam stabilizer prepared in Example 3 of this application at different pH values. Detailed Implementation

[0059] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0060] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.

[0061] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.

[0062] Example 1 This embodiment relates to a method for preparing a dual-response foam stabilizer, comprising the following steps: (1) Preparation of porous cellulose microspheres S1 dissolves hydroxypropyl methylcellulose in water to obtain a cellulose aqueous solution with a cellulose mass fraction of 10%, adds 30% calcium carbonate (particle size of 1 μm) as a physical pore-forming agent by cellulose mass, adjusts the pH to 10, and obtains the aqueous phase; S2 adds 2% polyglycerol monostearate (by weight of cyclohexane) as a dispersant to cyclohexane. After uniform dispersion by ultrasonication, an oil phase is obtained. Aqueous phase is then added dropwise under continuous stirring, with a volume ratio of oil phase to water phase of 5:1. After the dropwise addition is complete, 20% divinyl sulfone (by weight of cellulose) as a crosslinking agent is added. The temperature is raised to 50°C, and the mixture is refluxed for 6 hours under stirring at a stirring rate of 300 rpm. After the S3 reaction is completed, the microspheres are obtained by filtration and separation. Then, the microspheres are immersed in 0.5 mol / L HCl solution and stirred until no bubbles are generated. Finally, they are washed and dried to obtain porous cellulose microspheres. (2) Modification of porous cellulose microspheres S4. Porous cellulose microspheres were dispersed in a 1.5 mol / L NaOH solution at a concentration of 0.04 g / mL. Epichlorohydrin was added at a volume ratio of 0.5 mL / g to the mass of the porous cellulose microspheres. The mixture was reacted at 30 °C for 4 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain epoxidized cellulose microspheres. S5. Epoxidized cellulose microspheres were dispersed in a mixed solvent of isopropanol and water (volume ratio 4:1) to a dispersion concentration of 0.04 g / mL. Equal molar amounts of sodium chloroacetate and NaOH were added, with the mass of sodium chloroacetate being 1.5:1 of the mass of the epoxidized cellulose microspheres. The mixture was stirred at 55 °C for 3 h at a stirring rate of 300 rpm. After filtration, washing, and drying, modified porous cellulose microspheres were obtained. (3) The modified porous cellulose microspheres were dispersed in anhydrous ethanol at a concentration of 0.05 g / mL. After ultrasonic dispersion, a dispersion was obtained. Ammonia water with a mass fraction of 20% was added. The volume ratio of ammonia water to the mass of modified porous cellulose microspheres was 0.5 ml / g. An ethanol solution containing tetraethyl orthosilicate (volume fraction of tetraethyl orthosilicate of 25%) was added dropwise to the dispersion under stirring. The volume ratio of tetraethyl orthosilicate to the mass of modified porous cellulose microspheres was 1.5 ml / g. After the addition was completed, the mixture was reacted under stirring for 6 h. After the reaction was completed, the microspheres were separated, washed, and dried to obtain cellulose-silica composite microspheres. (4) The cellulose-silica composite microspheres were dispersed in anhydrous toluene at a concentration of 0.04 g / mL. After ultrasonic dispersion for 30 min, 3% of the mass of cellulose-silica composite microspheres of 3-aminopropyltriethoxysilane was added. The mixture was heated to 80 °C under nitrogen and refluxed for 24 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain the aminated composite microspheres. (5) Disperse the aminated composite microspheres in water to a concentration of 0.03 g / mL, add 0.5 mol / L dilute hydrochloric acid to adjust the pH to 3.5, add an aqueous solution containing cocamidopropyl hydroxysulfonate betaine (mass concentration of 0.5%), the mass of the amphoteric surfactant is 5% of the mass of the aminated composite microspheres, stir for 2 h, add 1 mol / L NaOH solution to adjust the pH to 7, filter, wash and dry to obtain the core layer; (6) The core layer was dispersed in a mixed solvent of ethanol and water (volume ratio of ethanol to water was 3:1) with a dispersion concentration of 0.04 g / mL. γ-methacryloxypropyltrimethoxysilane was added, and 0.5 mol / L dilute hydrochloric acid was added to adjust the pH to 4. After stirring at room temperature for 2 h, N-isopropylacrylamide, dimethylaminoethyl methacrylate, and ammonium persulfate (1% of the total molar amount of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltrimethoxysilane) were added. The total mass ratio of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltrimethoxysilane to the mass of the core layer was 0.3:1, and the molar ratio of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltrimethoxysilane was 14:3:1. The reaction was carried out under nitrogen at 60 °C for 6 h. After the reaction was completed, the core layer was separated, washed, and dried to obtain the final product.

[0063] Example 2 This embodiment relates to a method for preparing a dual-response foam stabilizer, comprising the following steps: (1) Preparation of porous cellulose microspheres S1 dissolves microcrystalline cellulose in water to obtain a cellulose aqueous solution with a cellulose mass fraction of 20%, adds 50% magnesium carbonate (particle size of 5μm), a physical pore-forming agent, to the cellulose mass, and adjusts the pH to 12 to obtain the aqueous phase; S2 adds 4% by weight of n-heptane dispersant Span 80 to cyclohexane and disperses it evenly by ultrasonication to obtain an oil phase. Aqueous phase is then added dropwise under continuous stirring, with a volume ratio of oil phase to water phase of 10:1. After the dropwise addition is complete, 50% by weight of cellulose crosslinking agent divinyl sulfone is added. The temperature is raised to 60°C and refluxed for 3 h under stirring at a stirring rate of 500 rpm. After the S3 reaction is completed, the microspheres are obtained by filtration and separation. Then, the microspheres are immersed in 1.5 mol / L HCl solution and stirred until no bubbles are generated. Finally, they are washed and dried to obtain porous cellulose microspheres. (2) Modification of porous cellulose microspheres S4. Porous cellulose microspheres were dispersed in a 2.5 mol / L NaOH solution at a concentration of 0.06 g / mL. Epichlorohydrin was added at a volume ratio of 2 mL / g to the mass of the porous cellulose microspheres. The mixture was reacted at 40 °C for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain epoxidized cellulose microspheres. S5. Epoxidized cellulose microspheres were dispersed in a mixed solvent of isopropanol and water (volume ratio 4:1) to a dispersion concentration of 0.06 g / mL. Equal molar amounts of sodium chloroacetate and NaOH were added, with the mass of sodium chloroacetate being 2.5:1 of the mass of the epoxidized cellulose microspheres. The mixture was stirred at 60 °C for 4 h at a stirring rate of 400 rpm. After filtration, washing, and drying, modified porous cellulose microspheres were obtained. (3) The modified porous cellulose microspheres were dispersed in anhydrous ethanol at a concentration of 0.08 g / mL. After ultrasonic dispersion, a dispersion was obtained. Ammonia water with a mass fraction of 30% was added. The volume ratio of ammonia water to the mass of the modified porous cellulose microspheres was 1 ml / g. An ethanol solution containing tetraethyl orthosilicate (with a volume fraction of 30% tetraethyl orthosilicate) was added dropwise to the dispersion under stirring. The volume ratio of tetraethyl orthosilicate to the mass of the modified porous cellulose microspheres was 2.5 ml / g. After the addition was completed, the mixture was reacted under stirring for 4 h. After the reaction was completed, the microspheres were separated, washed, and dried to obtain cellulose-silica composite microspheres. (4) The cellulose-silica composite microspheres were dispersed in anhydrous toluene at a concentration of 0.06 g / mL. After ultrasonic dispersion for 30 min, 3-aminopropyltriethoxysilane at 5% of the mass of the cellulose-silica composite microspheres was added. The mixture was heated to 110 °C under nitrogen and refluxed for 12 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain the aminated composite microspheres. (5) Disperse the aminated composite microspheres in water to a concentration of 0.05 g / mL, add 0.5 mol / L dilute hydrochloric acid to adjust the pH to 4.5, add an aqueous solution containing dodecyl dimethyl sulfobetaine (mass concentration of 5%), the mass of dodecyl dimethyl sulfobetaine is 15% of the mass of the aminated composite microspheres, stir for 4 h, add 1 mol / L NaOH solution to adjust the pH to 8, filter, wash and dry to obtain the core layer; (6) The core layer was dispersed in a mixed solvent of ethanol and water (volume ratio of ethanol to water was 3:1) with a dispersion concentration of 0.06 g / mL. γ-methacryloxypropyltriethoxysilane was added, and 0.5 mol / L dilute hydrochloric acid was added to adjust the pH to 5. After stirring at room temperature for 4 h, N-isopropylacrylamide, dimethylaminoethyl methacrylate, and potassium persulfate (3% of the total molar amount of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltriethoxysilane) were added. The total mass ratio of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltriethoxysilane to the mass of the core layer was 0.8:1, and the molar ratio of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltriethoxysilane was 16:5:1. The reaction was refluxed at 70 °C under argon for 4 h. After the reaction was completed, the core layer was separated, washed, and dried to obtain the final product.

[0064] Example 3 This embodiment relates to a method for preparing a dual-response foam stabilizer, comprising the following steps: (1) Preparation of porous cellulose microspheres S1 dissolves microcrystalline cellulose in water to obtain a cellulose aqueous solution with a cellulose mass fraction of 15%, adds calcium carbonate (particle size of 3μm) as a physical pore-forming agent with a cellulose mass fraction of 35%, adjusts the pH to 11, and obtains the aqueous phase; S2 adds 3% by weight of hexane dispersant Span 80 to cyclohexane and disperses it evenly by ultrasonication to obtain an oil phase. Aqueous phase is then added dropwise to the oil phase while continuously stirring, with a volume ratio of oil phase to water phase of 8:1. After the dropwise addition is complete, 35% by weight of cellulose crosslinking agent divinyl sulfone is added. The temperature is raised to 55°C and refluxed for 4.5 hours with stirring at a stirring rate of 400 rpm. After the S3 reaction is completed, the microspheres are obtained by filtration and separation. Then, the microspheres are immersed in 1 mol / L HCl solution and stirred until no bubbles are generated. Finally, they are washed and dried to obtain porous cellulose microspheres. (2) Modification of porous cellulose microspheres S4. Porous cellulose microspheres were dispersed in a 2 mol / L NaOH solution at a concentration of 0.05 g / mL. Epichlorohydrin was added at a volume ratio of 1 ml / g to the mass of the porous cellulose microspheres. The reaction was carried out at 35 °C for 6 h. After the reaction was completed, the microspheres were filtered, washed, and dried to obtain epoxidized cellulose microspheres. S5. Epoxidized cellulose microspheres were dispersed in a mixed solvent of isopropanol and water (volume ratio 4:1) to a dispersion concentration of 0.05 g / mL. Equal molar amounts of sodium chloroacetate and NaOH were added, with the mass of sodium chloroacetate being 2:1 of the mass of the epoxidized cellulose microspheres. The mixture was stirred at 58 °C for 3.5 h at a stirring rate of 400 rpm. After filtration, washing, and drying, modified porous cellulose microspheres were obtained. (3) The modified porous cellulose microspheres were dispersed in anhydrous ethanol at a concentration of 0.06 g / mL. After ultrasonic dispersion, a dispersion was obtained. Ammonia water with a mass fraction of 25% was added. The volume ratio of ammonia water to the mass of modified porous cellulose microspheres was 0.8 ml / g. An ethanol solution containing tetraethyl orthosilicate (volume fraction of tetraethyl orthosilicate of 27%) was added dropwise to the dispersion under stirring. The volume ratio of tetraethyl orthosilicate to the mass of modified porous cellulose microspheres was 2 ml / g. After the addition was completed, the mixture was reacted under stirring for 5 h. After the reaction was completed, the microspheres were separated, washed, and dried to obtain cellulose-silica composite microspheres. (4) Disperse cellulose-silica composite microspheres in anhydrous toluene at a concentration of 0.05 g / mL. After ultrasonic dispersion for 30 min, add 4% of 3-aminopropyltriethoxysilane by mass of cellulose-silica composite microspheres. Heat to 100 °C under nitrogen and reflux for 18 h. After the reaction, filter, wash and dry to obtain aminated composite microspheres. (5) Disperse the aminated composite microspheres in water to a concentration of 0.04 g / mL, add 0.5 mol / L dilute hydrochloric acid to adjust the pH to 4.5, add an aqueous solution containing cocamidopropyl hydroxysulfonate betaine (mass concentration of 3%), the mass of cocamidopropyl hydroxysulfonate betaine being 10% of the mass of the aminated composite microspheres, stir for 3 h, add 1 mol / L NaOH solution to adjust the pH to 8, filter, wash, and dry to obtain the core layer; (6) The core layer was dispersed in a mixed solvent of ethanol and water (volume ratio of ethanol to water was 3:1) to a dispersion concentration of 0.05 g / mL. 3-(acryloyloxy)propyltrimethoxysilane was added, and the pH was adjusted to 5 with 0.5 mol / L dilute hydrochloric acid. After stirring at room temperature for 3 h, N-isopropylacrylamide, dimethylaminoethyl methacrylate, and potassium persulfate (N-isopropylacrylamide, dimethylaminoethyl methacrylate, 3-(acryloyloxy)propyltrimethoxysilane) were added. The total mass of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltrimethoxysilane was 2% of the total molar mass of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltrimethoxysilane, with a mass ratio of 0.5:1 to the core layer and a molar ratio of 15:4:1 to N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloxypropyltrimethoxysilane, and the reaction was carried out under nitrogen at 65°C for 5 hours. After the reaction was completed, the mixture was separated, washed, and dried to obtain the final product.

[0065] Example 4 The difference between this embodiment and embodiment 3 is that cocamidopropyl betaine is used instead of cocamidopropyl hydroxysulfonate in step (5), while the rest are the same.

[0066] Example 5 The difference between this embodiment and Embodiment 3 is that the particle size of calcium carbonate in step S1 is 8 μm, while the rest are the same.

[0067] Example 6 The difference between this embodiment and embodiment 3 is that the mass fraction of ammonia in step (3) is 15%, while the rest are the same.

[0068] Example 7 The difference between this embodiment and embodiment 3 is that the mass fraction of ammonia in step (3) is 35%, while the rest are the same.

[0069] Comparative Example 1 The difference between this comparative example and Example 3 is that no pore-forming agent is added in step S1, that is, the microspheres do not contain pores, and silica only grows on the surface of the cellulose microspheres; the rest are the same.

[0070] Comparative Example 2 The difference between this comparative example and Example 3 is that step S4 is omitted, and step S5 involves dispersing porous cellulose microspheres in a mixed solvent of isopropanol and water for carboxymethylation modification. All other steps are the same.

[0071] Comparative Example 3 The difference between this comparative example and Example 3 is that step S5 is omitted, and only the porous cellulose microspheres are epoxidized; all other aspects are the same.

[0072] Comparative Example 4 The difference between this comparative example and Example 3 is that step (3) is not performed, that is, silica growth is not performed, and the modified porous cellulose microspheres are directly subjected to steps (4), (5), and (6), while the rest are the same.

[0073] Comparative Example 5 The difference between this comparative example and Example 3 is that step (4) is not performed, that is, the amination modification of the composite microspheres is not performed; all other steps are the same.

[0074] Comparative Example 6 The difference between this comparative example and Example 3 is that in step (6), the ratio of the total mass of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and silane coupling agent containing double bonds to the mass of the core layer is 1.1:1, while the rest are the same.

[0075] Comparative Example 7 The difference between this comparative example and Example 3 is that N-isopropylacrylamide, dimethylaminoethyl methacrylate, and a silane coupling agent containing double bonds are added simultaneously in step (6), while the rest are the same.

[0076] Comparative Example 8 The difference between this comparative example and Example 3 is that step (6) is omitted, i.e., there is no shell structure, while the rest are the same.

[0077] Comparative Example 9 The difference between this comparative example and Example 3 is that the preparation steps of the dual-response foam stabilizer are as follows: N-isopropylacrylamide, dimethylaminoethyl methacrylate and a silane coupling agent containing double bonds are homogeneously polymerized without a core layer, i.e., without steps (1)-(5). The specific steps are: 3-(acryloyloxy)propyltrimethoxysilane is added to a mixed solvent of ethanol and water (the volume ratio of ethanol to water is 3:1), 0.5 mol / L dilute hydrochloric acid is added to adjust the pH to 5, and the mixture is stirred at room temperature for 3 hours. Then, N-isopropylacrylamide, dimethylaminoethyl methacrylate, and potassium persulfate (2% of the total molar amount of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and 3-(acryloyloxy)propyltrimethoxysilane) were added. The molar ratio of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and γ-methacryloyloxypropyltrimethoxysilane was 15:4:1. The mixture was refluxed at 65°C under nitrogen for 5 hours. After the reaction was completed, the mixture was separated, washed, and dried to obtain the final product. All other steps were the same.

[0078] Test Example 1 The particle size (D50) of the foam stabilizers obtained in the above examples and comparative examples is shown in Table 1. The test method was to determine the particle size using a laser particle size analyzer (wet method). Table 1

[0079] Test Example 2 The foam stabilizers obtained in the above examples and comparative examples were tested for foam stability at different temperatures and pH values. The test data are shown in Tables 2 and 3. The test method was as follows: the foam stabilizer was mixed with sodium dodecyl sulfate at a mass ratio of 1:5 to prepare 200 mL of a 0.5% (total mass fraction) aqueous solution. The solution was stirred at 7000 rpm for 60 s, and the initial foam volume and half-life of the eluent were recorded. The pH value in Table 2 is 7, and the test temperature in Table 3 is 25℃.

[0080] Table 2

[0081] Table 3

[0082] In this application, as temperature increases, a higher half-life retention rate indicates better temperature response performance; as pH increases, a larger half-life difference indicates better pH response performance. Under the same conditions, a longer half-life indicates better foam stabilization performance.

[0083] According to the data in Tables 2 and 3, the half-life of all samples decreased with increasing temperature and pH, but the magnitude of the decrease varied significantly: the 80℃ / 25℃ half-life ratio of Examples 1-3 was 0.511~0.519, with a half-life difference of 30-33 min under acidic and alkaline conditions; while the 80℃ / 25℃ half-life ratio of Comparative Examples 1-8 was 0.340~0.469, with a half-life difference of ≤20 min under acidic and alkaline conditions; and the 80℃ / 25℃ half-life ratio of Comparative Example 9 was 0.289. This indicates that the dual-responsive shell and in-situ cross-linked network of the foam stabilizer prepared in this application significantly improve the foam stability retention ability under different temperature and pH conditions.

[0084] In Example 4, carboxybetaine was used instead of sulfobetaine. The half-life at different temperatures was lower than that in Example 3. This is because the carboxyl group of carboxybetaine is easily protonated at high temperatures, which reduces its hydrophilicity and weakens its interfacial activity; while sulfobetaine has better temperature resistance.

[0085] In Example 5, the particle size of the pore-forming agent increased, resulting in increased pore size, decreased specific surface area, reduced silica loading and surfactant grafting, weakened sustained-release function, and decreased half-life at different temperatures compared to Example 3.

[0086] In Example 6, the ammonia concentration was reduced, while in Example 7, the ammonia concentration was increased. The half-life at 25°C and 80°C decreased compared to Example 3. Too low an ammonia concentration resulted in a slow TEOS hydrolysis and condensation rate, insufficient silica growth, weakened Pickering stabilization effect and rigid support, and reduced sustained-release function. Too high an ammonia concentration led to excessively rapid hydrolysis of tetraethyl orthosilicate, potentially causing rapid condensation of silica at the pore openings, clogging the pores and affecting surfactant grafting and sustained-release function. However, the impact was less severe than in Example 6, indicating that the negative effects of high ammonia concentration were relatively controllable. The pH response performance of the foam stabilizers obtained in Examples 4-7 was not significantly different from that in Example 3.

[0087] The cellulose microspheres in Comparative Example 1 lacked pores, and the absence of pore structure led to a sharp decrease in specific surface area. Silica was only loaded on the outer surface, resulting in low loading and insufficient surfactant grafting, thus losing the sustained-release function. Therefore, the surfactant could not be replenished during the temperature response, causing the half-life at 80°C to decrease significantly compared to Example 3, and the half-life retention rate to decrease. At the same time, the pH response amplitude was small, indicating that the pH response of the shell could not be effectively converted into foam stabilizing performance when there were no pores.

[0088] The porous cellulose microspheres in Comparative Example 2 were not epoxidized, and the porous cellulose microspheres in Comparative Example 3 were not carboxymethylated. Both resulted in insufficient negative charge density on the surface, which affected the subsequent amination modification and surfactant grafting efficiency, and caused a significant decrease in the half-life at 80℃. When the pH changed, although the shell could respond, the total amount of surfactant that could be slowly released by the core layer was insufficient, and the interfacial replenishment capacity was limited, so the response amplitude decreased significantly.

[0089] In Comparative Example 4, no silica was grown. The absence of silica led to the loss of the Pickering stabilizing effect, insufficient rigid support, and a reduction in amination sites, resulting in a significant decrease in the half-life at 80°C. When pH changes triggered the shell response, although the foam stabilizer could migrate to the interface, the lack of a silica solid particle adsorption layer meant that the interface anchoring relied solely on the hydrophobic effect of the shell, resulting in insufficient anchoring strength and a significant decrease in the pH response amplitude.

[0090] In Comparative Example 5, without amination modification, the amphoteric surfactant could not be efficiently grafted through electrostatic attraction, and the half-life at 80°C decreased significantly, indicating that amination modification is crucial for surfactant grafting and silica-shell connection. When pH changes, although it can respond, the total amount of surfactant that can be slowly released in the core layer is seriously insufficient. Therefore, the effect of pH response on improving foam stability is limited, and the half-life is significantly lower than that of Example 3.

[0091] The shell obtained in Comparative Example 6 was too thick. The excessively thick shell led to a decrease in response sensitivity and a weakening of the driving force for migration to the interface. At the same time, the excessively thick shell hindered the slow-release diffusion of the surfactant, resulting in a significant decrease in the half-life at different temperatures compared to Example 3, and a significant decrease in the pH response amplitude.

[0092] When the monomers in Comparative Example 7 were added together, the half-life at different temperatures was significantly lower than that in Example 3, and the effect of pH response on foam stabilization performance was also greatly reduced. Simultaneously, the addition of monomers caused some of the double-bonded silane coupling agents to undergo homogeneous polymerization in solution, forming free copolymer chains instead of being anchored to the core surface. Insufficient covalent bonding between the core and shell led to easy desorption of the shell under shear conditions, resulting in the failure of response triggering and in-situ crosslinking functions.

[0093] Comparative Example 8 contains only a core layer structure, lacks temperature- and pH-responsive triggering mechanisms, and does not have a chemical cross-linking structure, resulting in a significant reduction in foam stabilization performance.

[0094] Comparative Example 9 lacks a core layer structure, thus lacking the Pickering stabilizing effect of silica, the sustained-release effect of surfactants, and the flexible support of cellulose. Therefore, the polymer cannot effectively anchor the interface after response, resulting in a significant decrease in half-life under temperature changes. Although the pH response amplitude is large, it cannot be converted into effective foam stabilizing performance, indicating that the pH response must work in conjunction with the complete core layer to play a role.

[0095] Test Example 3 The foam stabilizer obtained in Example 3 was tested for its foam stability at different temperatures and pH values. The test data are shown in Table 4. The test method was as follows: the foam stabilizer was mixed with sodium dodecyl sulfate at a mass ratio of 1:5 to prepare 200 mL of a 0.5% aqueous solution. The solution was stirred at 7000 rpm for 60 s, and the initial foam volume and half-life of the eluent were recorded. Figure 1 , Figure 2 .

[0096] Table 4

[0097] Based on the data in Table 4, Figure 1-2 It is known that the foam stabilizer prepared in this application has good temperature and pH response, and has good foam stabilizing effect in high temperature, acidic and alkaline reservoir environments.

[0098] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A dual-response foam stabilizer, characterized in that, It includes a core layer and a responsive copolymer shell layer covering the outer surface of the core layer; The core layer consists of porous cellulose microspheres, silica grown in the channels of the porous cellulose microspheres and on the surface of the microspheres, and amphoteric surfactants grafted onto the surface of the silica. The responsive copolymer shell is obtained by copolymerizing N-isopropylacrylamide, dimethylaminoethyl methacrylate, and a silane coupling agent containing double bonds.

2. The dual-response foam stabilizer according to claim 1, characterized in that, The porous cellulose microspheres were obtained through epoxidation and carboxymethylation modification.

3. The dual-response foam stabilizer according to claim 1, characterized in that, The amphoteric surfactant is cocamidopropyl hydroxysulfonate or dodecyl dimethyl sulfonate.

4. The dual-response foam stabilizer according to claim 1, characterized in that, The silane coupling agent containing double bonds is at least one of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, 3-(acryloxy)propyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.

5. The method for preparing the dual-response foam stabilizer according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Preparation of porous cellulose microspheres S1 dissolves cellulose in water to obtain a cellulose aqueous solution with a cellulose mass fraction of 10-20%, adds a physical porogen with a cellulose mass fraction of 30-50%, adjusts the pH to 10-12, and obtains the aqueous phase; S2. After adding a dispersant to the oil phase solvent and dispersing it evenly, an oil phase is obtained. A water phase is then added dropwise to it under stirring. The volume ratio of the oil phase to the water phase is (5-10):

1. After the dropwise addition is completed, a crosslinking agent is added. The temperature is raised to 50-60℃, and the reaction is carried out for 3-6 hours under stirring at a stirring rate of 300-500 rpm. After the S3 reaction is completed, the microspheres are obtained by filtration and separation. Then, the microspheres are immersed in HCl solution and stirred until no more bubbles are generated. Finally, they are washed and dried to obtain porous cellulose microspheres. (2) Modification of porous cellulose microspheres S4. Porous cellulose microspheres were dispersed in NaOH solution, and epichlorohydrin was added. The volume ratio of epichlorohydrin to the mass ratio of porous cellulose microspheres was 0.5-2 ml / g. The reaction was carried out at 30-40℃ for 4-6 h. After the reaction was completed, the microspheres were filtered, washed, and dried to obtain epoxidized cellulose microspheres. S5. Epoxidized cellulose microspheres were dispersed in a mixed solvent of isopropanol and water, and equimolar amounts of sodium chloroacetate and NaOH were added. The mass of sodium chloroacetate was (1.5-2.5):1 of the mass of the epoxidized cellulose microspheres. The mixture was stirred at 55-60℃ for 3-4 hours, filtered, washed, and dried to obtain modified porous cellulose microspheres. (3) The modified porous cellulose microspheres were dispersed in anhydrous ethanol and ultrasonically dispersed to obtain a dispersion. Ammonia water was added, and the volume ratio of ammonia water to the mass ratio of modified porous cellulose microspheres was 0.5-1 ml / g. An ethanol solution containing tetraethyl orthosilicate was added dropwise to the dispersion under stirring, and the volume ratio of tetraethyl orthosilicate to the mass ratio of modified porous cellulose microspheres was 1.5-2.5 ml / g. After the addition was completed, the mixture was reacted under stirring for 4-6 hours. After the reaction was completed, the mixture was separated, washed, and dried to obtain cellulose-silica composite microspheres. (4) Disperse cellulose-silica composite microspheres in anhydrous toluene, and after ultrasonic dispersion, add 3-5% of 3-aminopropyltriethoxysilane by mass of cellulose-silica composite microspheres. Heat to 80-110℃ and reflux for 12-24 h under inert gas protection. After the reaction, filter, wash and dry to obtain aminated composite microspheres. (5) Disperse the aminated composite microspheres in water, adjust the pH to 3.5-4.5, add an aqueous solution containing an amphoteric surfactant, the mass of which is 5-15% of the mass of the aminated composite microspheres, stir for 2-4 hours, adjust the pH to 7-8, filter, wash, and dry to obtain the core layer; (6) Disperse the core layer in a mixed solvent of ethanol and water, add a silane coupling agent containing double bonds, adjust the pH to 4-5, stir at room temperature for 2-4 h, and then add N-isopropylacrylamide, dimethylaminoethyl methacrylate, and initiator. The ratio of the total mass of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and silane coupling agent containing double bonds to the mass of the core layer is (0.3-0.8):1, and the molar ratio of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and silane coupling agent containing double bonds is (14-16):(3-5):

1. React at 60-70℃ under a protective gas atmosphere for 4-6 h. After the reaction is completed, separate, wash, and dry to obtain the final product.

6. The method for preparing the dual-response foam stabilizer according to claim 5, characterized in that, The cellulose mentioned in step S1 is hydroxypropyl methylcellulose or microcrystalline cellulose; The physical pore-forming agent is at least one of calcium carbonate, magnesium carbonate, and barium carbonate. The particle size of the physical porogen is 1-5 μm.

7. The method for preparing the dual-response foam stabilizer according to claim 5, characterized in that, The oil phase solvent mentioned in step S2 is at least one of cyclohexane, n-hexane, n-heptane, and cyclopentane; The dispersant is polyglycerol monostearate or Span 80, and its dosage is 2-4% of the mass of the oil phase solvent. The crosslinking agent is divinyl sulfone, and the amount used is 20-50% of the cellulose mass.

8. The method for preparing the dual-response foam stabilizer according to claim 6, characterized in that, The modified porous cellulose microspheres described in step (3) are dispersed in anhydrous ethanol at a concentration of 0.05-0.08 g / mL; The mass fraction of the ammonia solution is 20-30%. The volume fraction of tetraethyl orthosilicate in the ethanol solution containing tetraethyl orthosilicate is 25-30%.

9. The method for preparing the dual-response foam stabilizer according to claim 6, characterized in that, The dispersion concentration of the porous cellulose microspheres in the NaOH solution in step S4 is 0.04-0.06 g / mL; The dispersion concentration of the epoxidized cellulose microspheres in the mixed solvent in step S5 is 0.04-0.06 g / mL; The dispersion concentration of the cellulose-silica composite microspheres in anhydrous toluene in step (4) is 0.04-0.06 g / mL; The concentration of the aminated composite microspheres in water in step (5) is 0.03-0.05 g / mL.

10. The method for preparing the dual-response foam stabilizer according to claim 6, characterized in that, The dispersion concentration of the core layer microspheres in water in step (6) is 0.04-0.06 g / mL; The initiator is ammonium persulfate or potassium persulfate, and the amount used is 1-3% of the total molar amount of N-isopropylacrylamide, dimethylaminoethyl methacrylate, and silane coupling agent containing double bonds.

Citation Information

Patent Citations

  • A temperature-responsive nano foam stabilizer and a preparation method thereof, and a temperature-sensitive foaming agent and a preparation method thereof

    CN113912780B